PENGARUH STRES TENAGA KERJA TERHADAP KECELAKAAN KERJA PADA PELAKSANAAN PROYEK KONSTRUKSI DI SURABAYA YANG DIMODERASI USIA, PENDIDIKAN DAN PENGALAMAN KERJA - Muhammad Affandi Maulana; Feri Harianto; Fahmi Firdaus Alrizal; Diah Listyaningsih (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
The time constraint on implementing construction projects results in work stress on the workforce. Several factors that influence work stress in the force include age, education level, and work experience. Each crew has different levels of stress and trigger factors, from the level of stress experienced by workers from the lowest to the highest. For this reason, the project manager needs to manage stress in the workforce so that work accidents can be reduced. This study aims to determine the effect of work stress on work accidents based on the moderation of age, education level, and work experience. The research method uses a survey method with the measuring instrument. The sampling method used is accidental sampling, with the respondents being foremen, handymen, and workers. Respondents in the study amounted to 50 people. The analysis used is a linear regression with moderation. Based on the research analysis, the result is that work stress has a significant effect on work accidents (sig. < 0.05). At the same time, the moderating variables of age and education level did not significantly affect work accidents (sig. > 0.05). Increasing age and the higher education level of the workforce do not increase work accidents that occur. These two variables do not function as moderator variables but as independent variables. The moderating variable of work experience significantly affects work accidents (sig. < 0.05). The increase in the work experience of the workforce reduces work accidents. The work experience variable also functions as a pure moderator variable.